Timely and reliable packets delivery over internet of vehicles for road accidents prevention: a cross‐layer approach. Issue 5 (1st September 2016) - Eze, Elias C.; Zhang, Sijing; Liu, Enjie; Nweso, Emmanuel N.; Eze, Joy C.
Abstract : With the envisioned era of internet of things, all aspects of Intelligent Transportation Systems will be connected to improve transport safety, relieve traffic congestion, reduce air pollution, enhance the comfort of transportation and significantly reduce road accidents. In internet of vehicles, regular exchange of current position, direction, velocity and so on, enables mobile vehicles to predict an upcoming accident and alert the human drivers in time or proactively take precautionary actions to avoid the accident. The actualisation of this concept requires the use of channel access protocols that can guarantee reliable and timely broadcast of safety messages. This study investigates the application of network coding concept to increase content of every transmission and achieve improved broadcast reliability with less number of retransmissions. In particular, the authors proposed Code Aided Retransmission‐based Error Recovery (CARER) scheme, introduced a request‐to‐broadcast/clear‐to‐broadcast (RTB/CTB) handshake to overcome hidden node problem and reduce packets collision rate. In order to avoid broadcast storm problem associated with the use of RTB/CTB packet in a broadcast transmission, they developed a rebroadcasting metric used to successfully select a vehicle to rebroadcast the encoded message. The performance of CARER protocol is clearly shown with detailed theoretical analysis and further validated with simulation experiments.